Beyond Arrivals : Emerging Opportunities for Georgian Firms in Tourism Value Chains - World Bank (World Bank, Washington, DC, 2019)
Georgia’s current tourism offering is oriented toward low-spending neighboring markets and,although there is growth in high-spend global markets, the share is still very small. The majority of international visitor trips are from Georgia’s neighboring countries—Russia, Azerbaijan, Armenia and Turkey. This strong regional footprint is partly attributable to Georgia’s reputation during Soviet times as a recreational destination. Proximity, low prices, familiarity and language have contributed to this strong position. However, of Georgia’s top 15 source markets, tourists from Azerbaijan, Armenia and Turkey have the lowest average total trip expenditure and make the shortest trips. Although Georgia has seen very strong growth from China and India, arrivals to Georgia from the top global tourism source markets1 in 2018 represented only 7.3 percent of arrivals to the country. Georgia’s government is targeting high-growth, high-spend source markets. In 2015, the Government of Georgia (GoG) launched “Georgia Tourism 2025”; a 10-year vision and strategic plan for increasing the value and importance of tourism for the benefit of the country’s economy and ultimately its citizens. The plan—developed with support from the World Bank Group—included infrastructure development, country promotion, service quality improvement and tourism product diversification. Building on this plan, in 2018, GoG developed a marketing, branding and promotional strategy to communicate Georgia’s brand positioning, visual and verbal identity guidelines, and promotional objectives and target high growth, high-spend source markets. As Georgia’s source markets evolve, new GVC structures necessary to serve those markets will alsoemerge. GoG has identified 26 key source markets based on accessibility, economic factors, culturalrelations, and other factors such as the size of diaspora, historical ties and language barriers. A shift towards these new markets will also correspond to changes in consumer behavioral trends and tastes. This, coupled with global industry trends will see new value chain structures emerge, emphasizing activities with differing competitive forces, and presenting differing opportunities to create and retain value. Georgian firms may need support to respond to changes in emerging tourism GVCs and compete for higher-value-added activities. The report asks and answers two questions: i) How are emerging trends changing the structure of Tourism GVCs and how can Georgian firms benefit from these changes? ii) What policy reforms, capital investment or skills development is needed to increase Georgia’s value chain competitiveness in each of these key tourism offerings?